Effects of different online modes on negotiation of meaning for learners of Chinese as a foreign language - An exploratory study - Jing Yan, Scott Grant, Hui Huang (Educational Technology & Society)
Many studies have examined the factors that influence second language interaction, such as task type and communication mode, i.e., face-to-face and computer-mediated communication through online mode. However, there is a paucity of research that has investigated the effects of task type on negotiation of meaning (NoM), a specific type of interaction, via different online modes, such as video/audio/text-based tools and virtual worlds. This study examined how the task type and online modes (Zoom and Second Life, a 3D virtual world) influenced NoM strategies among thirty-four university students learning Chinese as a foreign language. Participants were paired up and then participated in either a Zoom group or a Second Life group. Both groups completed the same information gap task and decision-making task. The recorded oral interactions were analysed in terms of the amount of talk, time on tasks, and NoM strategies. The findings showed that the information gap task produced more target language and NoM strategies than the decision-making task. Additionally, Zoom elicited more target language than Second Life, whereas Second Life produced more NoM strategies than Zoom. A potential interaction effect between task type and online mode on NoM strategies was also identified. The study sheds light on the factors that affected foreign language interaction and provides insights into the affordances that different online modes could provide to foreign language teaching and learning.